2002
DOI: 10.1074/jbc.m111818200
|View full text |Cite
|
Sign up to set email alerts
|

Two Defective Heterozygous Luteinizing Hormone Receptors Can Rescue Hormone Action

Abstract: Luteinizing hormone receptor is a G protein-coupled receptor and consists of two halves: the N-terminal extracellular half (exodomain) and C-terminal membraneassociated half (endodomain). Hormone binds to the exodomain, and the resulting hormone-exodomain complex modulates the endodomain to generate signals. There are mutations that impair either hormone binding or signal generation. We report that the coexpression of a binding defective mutant and a signal-defective mutant rescues signal generation to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 40 publications
(60 reference statements)
3
38
0
Order By: Relevance
“…Evidence pointing toward this goes back to as early as the 1980s when data from equilibrium sedimentation of detergent-solubilized LHR and radiation inactivation of LHRs on gonadal cells suggested that the LHR may be present in a dimeric or oligomeric form (31,32). More recently, functional complementation studies further suggested the dimerization of the LHR (33,34). Direct evidence in support of dimerization of the LHR has been obtained using fluorescent resonance energy transfer (FRET) (35)(36)(37)(38) as well as our studies demonstrating specific co-immunoprecipitation of differentially tagged forms of the LHR (39).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Evidence pointing toward this goes back to as early as the 1980s when data from equilibrium sedimentation of detergent-solubilized LHR and radiation inactivation of LHRs on gonadal cells suggested that the LHR may be present in a dimeric or oligomeric form (31,32). More recently, functional complementation studies further suggested the dimerization of the LHR (33,34). Direct evidence in support of dimerization of the LHR has been obtained using fluorescent resonance energy transfer (FRET) (35)(36)(37)(38) as well as our studies demonstrating specific co-immunoprecipitation of differentially tagged forms of the LHR (39).…”
mentioning
confidence: 66%
“…To examine the potential homodimerization/oligomerization of a signaling inactive hLHR mutant, we initially tested hLHR(K605R), which had previously been reported (using an alternate nomenclature as K583R) to be signaling inactive (33,34). However, when compared with cells expressing the same cell surface density of WT hLHR, we found K605R responded to hCG with ϳ30% of the maximal cAMP response of the WT hLHR.…”
Section: Resultsmentioning
confidence: 99%
“…We selected two LHR mutant receptors for their inability to bind the ligand (LH or hCG) or to transduce signaling after ligand binding. The first mutant receptor (LHR LH− ) harbored an inactivating Cys 22 to Ala 22 mutation in the ligand binding extracellular domain (35,36). The second mutant (LHR cAMP− ) contained a deletion of TM helices 6 and 7 in exon 11 (amino acids deleted from Val 553 to Ala 689 ), and it was chosen because of involvement of the deleted region in G protein coupling and second messenger generation (37).…”
Section: Resultsmentioning
confidence: 99%
“…There is recent functional evidence that the class A GPCRs for glycoprotein hormones [i.e., of LH/choriongonadotropin (hCG), FSH, and TSH] could transduce their signal in cultured cells as di/ oligomers by trans-activation (8,10,14,35) (Fig. 1B), henceforth termed intermolecular cooperation.…”
mentioning
confidence: 99%
“…However, for the luteinizing hormone receptor, which also has a long N-terminal domain that binds the ligand, partial reconstitution of function has been achieved by co-expression of distinct pairs of mutants (15)(16). Furthermore, in recent studies co-expression of a mutant receptor defective in hormone binding and another mutant defective in signal generation rescued hormone-activated cAMP production (17).…”
Section: Mutation Of a Highly Conserved Leucine In Intracellular Loopmentioning
confidence: 99%